Human decellularized adipose matrix derived hydrogel assists mesenchymal stem cells delivery and accelerates chronic wound healing. Issue 8 (9th December 2020) - Chen, Zhaoyang; Zhang, Bowen; Shu, Jun; Wang, Haiyang; Han, Yudi; Zeng, Quan; Chen, Youbai; Xi, Jiafei; Tao, Ran; Pei, Xuetao; Yue, Wen; Han, Yan
Abstract: Biological scaffolds based stem cell delivery methods have emerged as a promising approach for tissue repair and regeneration. Here we developed a hydrogel biological scaffold from human decellularized adipose matrix (hDAM) for human adipose‐derived stem cells (hASCs) delivery to accelerate chronic wound healing. The hDAM hydrogel was prepared by pepsin mediated digestion and pH controlled neutralization. The morphology, survival, proliferation, and angiogenic paracrine activity of hASCs cultured in the hydrogel were assessed. Moreover, the therapeutic efficacy of the hASCs‐hydrogel composite for impaired wound healing was evaluated by using a full‐thickness wound model on diabetic mouse. The developed hDAM hydrogel was a thermosensitive hydrogel, presented the biochemical complexity of native extracellular matrix and formed a porous nanofiber structure after gelation. The hydrogel can support hASCs adhesion, survival, and proliferation. Compared to standard culture condition, hASCs cultured in the hydrogel exhibited enhanced paracrine activity with increased secretion of hepatocyte growth factor. In the diabetic mice model with excisional full‐thickness skin wounds, mice treated with the hASCs‐hydrogel composite displayed accelerated wound closure and increased neovascularization. Our results suggested that the developed hDAM hydrogel can provide a favorable microenvironment for hASCs with augmented regeneration potential to accelerate chronic wound healing. Abstract :